Analysis of The Book “Manhaj at Tarbiyah an Nabawiyah li at Thifl” About Teacher Obligations to Educate Children - Melani Putri; Muhammad Akmansyah; Amiruddin Amiruddin (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
History has documented that teachers contributed to the development of Islamic education. It becomes a problem when several trends in teacher behavior need to be corrected and seem to damage the image of the teacher profession. In educating his students, the Teacher may give lessons and punish them through sanctions. In some cases, teachers have a dilemma; on the one hand, teachers must enforce school discipline and discipline. On the other, they are worried about being criminalized by parents or non-governmental organizations (NGOs) that defend children on charges of violence against children. This research is a descriptive study research library, which is a study that aims to provide an overview of the analysis of the book Manhaj At Tarbiyah An Nabawiyah Li At Thifl. This study found that: (1) teachers are obliged to provide convenience in solving children's problems by straightening out children's mistakes and thinking so as not to be mistaken. (2) the obligation of the Teacher as a proofreader requires the Teacher to understand when to be positive or when to be negative in correcting the child's mistakes by paying attention to the right time to guide the child. (3) Teachers must instill and uphold religious values ​​in their students from an early age so that they are accustomed to being educated in good things. (2) the obligation of the Teacher as a proofreader requires the Teacher to understand when to be positive or when to be negative in correcting the child's mistakes by paying attention to the right time to guide the child. (3) Teachers must instill and uphold religious values ​​in their students from an early age so that they are accustomed to being educated in good things. (2) the obligation of the Teacher as a proofreader requires the Teacher to understand when to be positive or when to be negative in correcting the child's mistakes by paying attention to the right time to guide the child. (3) Teachers must instill and uphold religious values ​​in their students from an early age so that they are accustomed to being educated in good things.